2011
DOI: 10.1037/a0024129
|View full text |Cite
|
Sign up to set email alerts
|

What is it about Picasso? Infants' categorical and discriminatory abilities in the visual arts.

Abstract: Research on infants' early development of aesthetic perception has focused on their ability to discriminate and evaluate auditory stimuli such as musical intervals or faces differing along their level of attractiveness. However, infants' discriminatory and evaluative responses in the domain of the visual arts have, as of today, not been examined. Artistic paintings are complex visual stimuli. Multiple cues such as color, style of brushing, common subjects, and others must be considered to discriminate and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Thus, it is clear that infants do show a keen ability to both discriminate and prefer certain art to other art, and this preference is likely due to an attraction to certain visual elements. We hope to expand on Cacchione et al (2011) by providing a more rigorously controlled study, exploring infant and adult preferences for original over systematically altered nonrepresentational art.…”
Section: Studies Of Infant Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is clear that infants do show a keen ability to both discriminate and prefer certain art to other art, and this preference is likely due to an attraction to certain visual elements. We hope to expand on Cacchione et al (2011) by providing a more rigorously controlled study, exploring infant and adult preferences for original over systematically altered nonrepresentational art.…”
Section: Studies Of Infant Perceptionmentioning
confidence: 99%
“…Finally, in the first article, to date, that has explored infant perception of visual art, Cacchione, Mohring, and Bertin (2011), from the University of Zurich, tested infants' ability to categorize paintings based on genre-impressionist compared with cubist. They found that infants were able to discriminate and categorize paintings by Monet from paintings by Picasso.…”
Section: Studies Of Infant Perceptionmentioning
confidence: 99%
“…In children aesthetic appreciation also depends on their level of neurocognitive development, which will limit the aspects of the artwork and intentions of the artist that they are able to process and understand (see Callaghan and Rochat, 2003 ). For example, aesthetic appreciation in infants who are too young (<1 year) to understand the representational nature of images is strongly influenced by the color and the visual pattern of the artwork, as measured by their allocation of attention (Cacchione et al, 2011 ). Once children understand the dual representational nature of pictures (i.e., that a picture is both an object itself and a symbol of something else; DeLoache and Burns, 1994 ) subject matter becomes more important in aesthetic appreciation (Gordon, 1952 ; Machotka, 1966 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, like adults, 6-month-old infants favor abstract art with contrast and complexity intact ( Krentz and Earl, 2013 ). And although infants do not always have the same visual aesthetic values as adults, babies still have clear preferences ( Cacchione et al, 2011 ; Taylor et al, 2013 ). Similar results are obtained in the domain of music.…”
Section: What Are Aesthetic Values?mentioning
confidence: 99%